Recent Advances in Transition-Metal-Free Aryl C–B Bond Formation - Chen, Kai; Wang, Linghua; Meng, Ge; Li, Pengfei (Synthesis, 2017)
Arylboronic acids and their derivatives are widely used in organic synthesis. Conventional methods for their preparation require either reactive organometallic reagents or transition-metal-mediated processes. In recent years, transition-metal-free reactions for aryl C–B bond formation that obviate preformed organometallic reagents have gained interest and have developed rapidly. These new reactions have shown significant advantages for the preparation of functionalized molecules. In this review, an overview of the recent advances in transition-metal-free aromatic borylation reactions is provided.1 Introduction2 Transition-Metal-Free Transformations of CAr–N Bonds to CAr–B Bonds3 Transition-Metal-Free Transformations of CAr–X Bonds to CAr–B Bonds4 Transition-Metal-Free Transformations of CAr–H Bonds to CAr–B Bonds5 Conclusion
Keywords: arenes; cross-coupling; boron; radical reaction; photochemistry